2017
DOI: 10.1186/s13256-017-1467-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary small cell carcinoma of the breast: a case report

Abstract: BackgroundNeuroendocrine breast cancer is a rare entity that was defined in 2003 by the World Health Organization as a separate breast cancer subtype. The diagnosis of neuroendocrine breast cancer requires the presence of neuroendocrine features in at least 50% of malignant cells, the exclusion of non-mammary primary tumors, as well as the presence of an in situ component in breast histology. The treatment and prognosis of neuroendocrine breast cancer are still not well established. Small cell carcinoma of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…Small cell carcinoma, whether the primary site is the breast or any other site of the body, the histopathologic features and immunohistochemical findings are the same. Therefore, to diagnose a primary breast small cell carcinoma we need to exclude if there is any other primary cancer outside the breast with the help of imaging studies, neuroendocrine differentiation not less than 50%, and/or presence of in situ carcinoma component histologically [ 4 ]. A case reported by Adegbola et al [ 1 ] exhibited foci of an in situ component of neuroendocrine pattern which confirms the primary breast origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small cell carcinoma, whether the primary site is the breast or any other site of the body, the histopathologic features and immunohistochemical findings are the same. Therefore, to diagnose a primary breast small cell carcinoma we need to exclude if there is any other primary cancer outside the breast with the help of imaging studies, neuroendocrine differentiation not less than 50%, and/or presence of in situ carcinoma component histologically [ 4 ]. A case reported by Adegbola et al [ 1 ] exhibited foci of an in situ component of neuroendocrine pattern which confirms the primary breast origin.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal markers (ER or PR) were positive in 35–54% of cases and HER2-neu was almost always negative [ 9 ]. The case reported by Abou Dalle et al [ 4 ] was receiving tamoxifen since progesterone receptor was positive in 20% of the tumor cells. Her2-neu, PR, and ER were negative in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is high time that a well-researched, objectively proven guidelines for treatment of this rare entity is placed on record. Yet the best management algorithm is still an enigma and prognosis for PSCNET breast is not established [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the leading cause of cancerrelated death in women. With an incidence of <1%, primary small cell neuroendocrine tumors (PSCNET) of breast, are a rare entity, amongst all breast malignancies [1,2]. First described in 1983, by Wade et al, there are fewer than hundred cases reported in medical literature [3].…”
Section: Introductionmentioning
confidence: 99%